Peran Brand Image, Elektronic Word Of Mouth Dan Brand Experience Dalam Mempengaruhi Keputusan Pembelian Pelanggan (Studi Kasus Pada Brand Sepatu Ventela) - Ramadhan, Dite Fathur; Mawardi, Moh Cholid; Basalamah, Muhammad Ridwan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study was conducted on UNISMA students who are actively studying at the Islamic University of Malang who have Ventela shoes, Jl. Mayjen Haryono 193, Dinoyo, Lowokwaru District, Malang City, East Java. The purpose of the study was to determine whether the Role of Brand Image, Electronic Word of Mouth, and Brand Experience influence Customer Purchasing Decisions. The type of research used is quantitative research with a questionnaire distribution method. The sample in this study was 70 respondents and data processing used the SPSS computer program. The variables used in this study are Customer Purchasing Decisions (dependent variables), while the independent variables are the Role of Brand Image, Electronic Word of Mouth, and Brand Experience. This study has met the requirements of validity and reliability. Data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and analysis of the coefficient of determination. The results of this study conclude that the variables Brand Image, Electronic Word of Mouth, and Brand Experience have a significant positive effect on Customer Purchasing Decisions, for Ventela shoes, they should be able to improve their brand reputation by developing themselves to continue to be able to create new things that are in accordance with the needs of society in current conditions. Keywords: Role of Brand Image, Electronic Word of Mouth, Brand Experience, Purchasing Decisions